2016
DOI: 10.1038/ncomms12061
|View full text |Cite
|
Sign up to set email alerts
|

Wars2 is a determinant of angiogenesis

Abstract: Coronary flow (CF) measured ex vivo is largely determined by capillary density that reflects angiogenic vessel formation in the heart in vivo. Here we exploit this relationship and show that CF in the rat is influenced by a locus on rat chromosome 2 that is also associated with cardiac capillary density. Mitochondrial tryptophanyl-tRNA synthetase (Wars2), encoding an L53F protein variant within the ATP-binding motif, is prioritized as the candidate at the locus by integrating genomic data sets. WARS2(L53F) has… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 55 publications
4
62
0
Order By: Relevance
“…A recently generated targeted Wars2 rat model supports our hypothesis: While, like in uncharacterized Wars2 knockout mice (URL: http://www.informatics.jax.org/), the Wars2 ‐deficient allele is embryonically lethal in a homozygous state ( Wars2 −/− ), heterozygous animals ( Wars2 − / + ) appear normal. Moreover, it has been shown that animals heterozygous ( Wars2 − /L53F ) for the knockout allele and Wars2 p.Leu53Phe, a common variant in rat strains that is associated with a 40% reduction in Wars2 activity, revealed diminished cardiac angiogenesis and reduced coronary flow as compared with animals with compound heterozygosity for the WT allele and the p.Leu53Phe allele ( Wars2 +/L53F ) (Wang et al., ). This suggests that Wars2 − /L53 represents a compound hypomorph similar to the situation observed in our patients.…”
Section: Discussionmentioning
confidence: 99%
“…A recently generated targeted Wars2 rat model supports our hypothesis: While, like in uncharacterized Wars2 knockout mice (URL: http://www.informatics.jax.org/), the Wars2 ‐deficient allele is embryonically lethal in a homozygous state ( Wars2 −/− ), heterozygous animals ( Wars2 − / + ) appear normal. Moreover, it has been shown that animals heterozygous ( Wars2 − /L53F ) for the knockout allele and Wars2 p.Leu53Phe, a common variant in rat strains that is associated with a 40% reduction in Wars2 activity, revealed diminished cardiac angiogenesis and reduced coronary flow as compared with animals with compound heterozygosity for the WT allele and the p.Leu53Phe allele ( Wars2 +/L53F ) (Wang et al., ). This suggests that Wars2 − /L53 represents a compound hypomorph similar to the situation observed in our patients.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, many studies have shown that ARSs participate in a variety of physiological and pathological processes through certain non-normative functions such as angiogenesis, post-translational modifications, translation initiation, and autophagy regulation [6][7][8][9] . For example, seryl-tRNA synthetase (SerRS) could bind to transcription factor Yin Yang 1 (YY1) to form a SerRS/YY1 complex, which interacted with distal cis-regulatory elements and then negatively regulated vascular endothelial cell growth factor A transcription during angiogenesis 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Traditional quantitative trait locus studies, with the need for lengthy fine-mapping and testing of candidate genes, continue to give valuable insights (for example Zhao et al, 2015; Fernandez-Duenas et al, 2015; Wang et al, 2016, and reviewed in Yau and Holmdahl, 2016), but, as with research using other model organisms, these approaches are being replaced by gene targeting using CRISPR/Cas9 and other techniques, as exemplified by the GERRC programme () and the osteocalcin study in this issue (Lambert et al, 2016). These programmes use gene targeting to knock out genes implicated in the aetiology of common human diseases via genome-wide association studies (GWAS) or other patient-based studies, and allow analysis of gene function that will give insights into disease pathogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…1). High-profile research groups across the world and strong ongoing programmes for generating rat knockouts (NIH GERRC and EU ELABORATE) take advantage of the genome-editing tools and technologies now in place to use the rat model as a springboard for giving insights into human disease (Zhao et al, 2015; Fernandez-Duenas et al, 2015; Wang et al, 2016). In this issue of Disease Models & Mechanisms (DMM), we are pleased to launch a timely Special Collection entitled Spotlight on Rat: Translational Impact , which highlights the strengths and ongoing commitment of researchers and funders to studies of the rat model for generating insights into mechanisms underlying human disease.…”
Section: Putting the ‘Rat’ In Laboratorymentioning
confidence: 99%